(untitled) (INNOVATIVE ECONOMY, 2025)
Zhuk V.M. THE SCIENTIFIC PRINCIPLES OF INSTITUTIONAL TRANSFORMATION OF THE AGRARIAN SYSTEM OF UKRAINE IN THE CONDITIONS OF POST-WAR EUROPEAN INTEGRATION Purpose. The article aims to develop the scientific principles for the institutional transformation of the agrarian system in the conditions of post-war inclusive challenges and Ukraine’s European integration. Methodology of research. The methodological basis of the study is a comprehensive interdisciplinary approach to the study of complex socio-economic phenomena, integrating the principles of economic theory, institutionalism, management, public administration, and behavioural economics. To achieve the set goal, the systems approach, modelling, methods of analysis and synthesis, and abstract and logical and monographic methods were used. This study employs a systems approach to examine the agricultural system as an integrated set of institutions; a modelling method to justify directions for its transformation in accordance with EU standards; and analysis and synthesis to assess the current state of the agricultural sector and identify institutional constraints. The abstract and logical method was used to formulate theoretical generalizations and conclusions; the monographic method – to study scientific approaches and summarize international experience; and the comparative method – to compare the institutional models of Ukraine and EU countries. Findings. The article shows that it is advisable to view the agrarian system not as a set of individual parameters for the development of the agricultural sector or rural areas, but as a holistic socio-economic institution in which formal institutions (“rules of the game”), informal institutions, and “organizations” interact. It was substantiated that limiting reform to the legislative and program documents alone does not yield deep transformations, as it ignores the influence of informal institutions, institutional interests, and the real capacity of organizations to implement changes. The author proposes a model of the agrarian system that reflects the relationships among the institutional environment, the functioning of organizations, the content of agrarian policy, and the desired order of socio-economic life in rural areas. The meaning of the concepts of “agrarian system”, “model of agrarian system”, and “state agrarian policy” is clarified. Originality. For the first time, a model of the agrarian system institute has been systematically formed with the separation and mutual coordination of its main components: informal institutions, formal institutions, and organizations, the functionality of which is revealed through vision, policy, reforms, and management. The conceptual and categorical support for agrarian policy has been further developed. Practical value. The proposed model approach can be used to improve state agrarian policy, its socialization, and its realization of the national interests of Ukraine in the conditions of post-war reconstruction and European integration. The proposed theoretical and methodological provisions provide the basis for the development of village-preserving, inclusive, and pro-European models of rural area development. Key words: institutional theory, agrarian system, rural areas, informal institutions, formal institutions, agrarian policy.